2017
DOI: 10.1126/scisignal.aan6284
|View full text |Cite
|
Sign up to set email alerts
|

Activation of master virulence regulator PhoP in acidic pH requires the Salmonella -specific protein UgtL

Abstract: The ability to respond to changes in pH is critical for all organisms. In Salmonella enterica, the sensor PhoQ responds to a mildly acidic pH by phosphorylating, and thereby activating, the virulence regulator PhoP. This PhoP/PhoQ two-component system is conserved in a subset of Gram-negative bacteria. PhoQ has been thought to be sufficient to activate PhoP in mildly acidic pH. However, we found that the Salmonella-specific protein UgtL, which was horizontally acquired by Salmonella before the divergence of S.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
73
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(75 citation statements)
references
References 75 publications
2
73
0
Order By: Relevance
“…whereas acidic pH activation of PhoP and downstream subset PhoPactivated genes require the Salmonella-specific protein UgtL (Choi & Groisman, 2017). Our data confirmed that the activation of pagR by PhoP/Q in response to low Mg 2+ requires mgtA.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…whereas acidic pH activation of PhoP and downstream subset PhoPactivated genes require the Salmonella-specific protein UgtL (Choi & Groisman, 2017). Our data confirmed that the activation of pagR by PhoP/Q in response to low Mg 2+ requires mgtA.…”
Section: Discussionsupporting
confidence: 80%
“…vated by different signals(Groisman & Mouslim, 2006;Park & Groisman, 2014). For example, low Mg 2+ activation of PhoP and over half of the downstream PhoP-activated genes require the Mg 2+ transporter MgtA(Park & Groisman, 2014), whereas acidic pH activation of PhoP and downstream subset PhoPactivated genes require the Salmonella-specific protein UgtL(Choi & Groisman, 2017). For example, low Mg 2+ activation of PhoP and over half of the downstream PhoP-activated genes require the Mg 2+ transporter MgtA(Park & Groisman, 2014), whereas acidic pH activation of PhoP and downstream subset PhoPactivated genes require the Salmonella-specific protein UgtL(Choi & Groisman, 2017).…”
mentioning
confidence: 99%
“…PhoP is a response regulator, forming a two-component regulatory system with its cognate sensor kinase, PhoQ. The active form of phosphorylated PhoP (PhoPϳP) controls the expression of target genes (55,56), including those encoded on Salmonella pathogenicity islands 1 and 2 (SPI-1 and SPI-2). In general, the expression of SPI-1 is negatively (57) and that of SPI-2 genes is positively controlled by PhoPϳP (58).…”
Section: Resultsmentioning
confidence: 99%
“…1B) (17, 29, 30). However, these sensors differ in that PmrB responds to a mildly acidic pH through protonation of periplasmic histidine residues (17), whereas PhoQ does so through its cytoplasmic region via a mechanism that does not involve histidine residues (31).…”
Section: Resultsmentioning
confidence: 99%
“…However, these sensors differ in that PmrB responds to a mildly acidic pH through protonation of periplasmic histidine residues (17), whereas PhoQ does so through its cytoplasmic region via a mechanism that does not involve histidine residues (31). In addition, full activation of the PhoP/PhoQ system under mildly acidic pH requires the PhoP-activated gene ugtL , which encodes a protein that stimulates PhoQ autophosphorylation (30). …”
Section: Resultsmentioning
confidence: 99%